Analisis Makkiy wal Madani menurut Perspektif Imam Suyuti pada Kitab Al Itqon - Ali Akbar; Meilisa Rahmanita; Aji Febriansyah (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2024)
This research reviews the differences, opinions of ulama, and special characteristics of the Makkiy and Madani verses in Al Itqon. This research is a comparative research by Al Imam Jalaluddin Abdurrahman ibn Abu Bakar Asy Suyuti who continued writing the book of interpretations of Jalalain after his teacher, Imam Jalaluddin Al Mahalli, died in 1505. In this research, we will use a comparative research model that explains the comparison of several problems, but very focused on the book Al Itqon by Imam Jalaluddin Asy Syuyuti.